THE EFFECTS OF THE COVID-19 ON PREPARATION STUDENTS FOR THE UNIVERSITY ENTRANCE EXAM: QUALITATIVE STUDY - YAVAŞ ÇELİK, Melike and ÖZTÜRK ÇOPUR, Ebru (Göbeklitepe Medical Science Journal, 2021)
Aim:It is aimed to examine the effects of the Covid-19 epidemic on the psychological, social and family relationship, exam preparation process of students preparing for the university entrance exams. Method:Universe selection has not been made. Participants were reached using the snowball sampling method.In this phenomenological qualitative study, four main themes were created with the method of description and examined. Results:It has been determined four theme that the Covid-19 epidemic process affects students’ psychological, social and family relationships, and their exam preparation processes. Conclusion:This study has shown that the pandemic process negatively affects the mental health of young people and that the family and friends relations of the young people deteriorate. In addition, it has been revealed that the preparation for the university entrance exam, which affects the lives of young people, has turned into a huge chaos due to the pandemic, and have difficulty coping with this process. Young people who experience excessive anxiety and fear experience uncertainties about their future.